A Novel Miniaturized Dual Slant-Polarized UWB Antenna Array with Excellent Pattern Symmetry Property for MIMO Applications - Zhi Zeng; Jianjun Huang; Zhaohui Song; Qinyu Zhang (International Journal of Antennas and Propagation)
A novel miniaturized 1 × 10 uniform linear dual slant-polarized UWB antenna array for MIMO base station is presented. The antenna array operates in the frequency band from 1710 to 2690 MHz with a 17.3–18.7 dBi gain in a size of 105 × 1100 × 37 mm. The array element is composed of two single-polarized dipoles evolved from bow-tie antenna with slots on them, which miniaturize the size of the antenna. The 10 array elements are fed through an air dielectric strip-line power splitter. Two parameters, the beam tracking and the beam squint, are presented to quantitatively describe the pattern symmetry property of the antenna. The simulated and measured radiation performances are studied and compared. The results show that the pattern symmetry property of the single antenna element has been improved about 24% compared with the former study, and the antenna array also provides excellent pattern symmetry property.